Fluorometabolite Natural Products - นาสมใจ, พิทักษ์ (KKU Science Journal, 2013)
Fluorine is ranked 13th most abundant element in the Earth’s crust and the most abundance halogen. However, fluorometabolites are exceedingly rare and only 15 compounds have been officially identified confining in plants and two bacteria. In this article the discovery, biosynthetic pathways, and bioactivities of fluorometabolites are reviewed. In particular, the most advanced study in bacterium Strptomyces cattleya is highlighted. The discovery of Fluorinase enzyme and its application as a synthetic tool for instalment of a C-F bond to organic molecules is also discussed.